Characteristics of the Patients Aged Less than 40 Years Operated for a Renal Mass (Journal of Kidney Cancer, 2023)
The incidence of renal cell cancer (RCC) is low in individuals aged less than 40 years; however several studies have shown this increasing trend over the years. Hereditary syndromes are associated with RCC and are more frequently observed in early-onset cases. In this study, we investigated the characteristics of the patients, aged less than 40 years, who were operated for a renal mass with the suspicion of RCC. We analyzed patients aged